C/2014 UN271(Bernardinelli-Bernstein): The Nearly Spherical Cow of Comets - Bernardinelli, Pedro H.; Bernstein, Gary M.; Montet, Benjamin T.; Weryk, Robert; Wainscoat, Richard; Aguena, M.; Allam, S.; Andrade-Oliveira, F. [UNESP]; Annis, J.; Avila, S.; Bertin, E.; Brooks, D.; et al. (American Astronomical Society, 2021)
Comet C/2014 UN271 (Bernardinelli-Bernstein), incoming from the Oort cloud, is remarkable in having the brightest (and presumably largest) nucleus of any well-measured comet and having been discovered at the heliocentric distance r h ≈ 29 au, farther than any Oort cloud comet. In this work, we describe the discovery process and observations and the properties that can be inferred from images recorded until the first reports of activity in 2021 June. The orbit has i = 95°, with a perihelion of 10.97 au to be reached in 2031 and a previous aphelion at 40,400 ± 260 au. Backward integration of the orbit under a standard Galactic tidal model and known stellar encounters suggests a perihelion of q ≈ 18 au on its previous perihelion passage 3.5 Myr ago; hence, the current data could be the first ever obtained of a comet that has not been inside Uranus's orbit in 4 Gyr. The photometric data show an unresolved nucleus with absolute magnitude H r = 8.0, colors that are typical of comet nuclei or Damocloids, and no secular trend as it traversed the range 34-23 au. For the r-band geometric albedo p r , this implies a diameter of km. There is strong evidence of brightness fluctuations at the ±0.2 mag level, but no rotation period can be discerned. A coma, nominally consistent with a stationary1/ρ surface brightness distribution, grew in scattering cross section at an exponential rate from A f ρ ≈ 1 to ≈150 m as the comet approached from 28 to 20 au. The activity rate is consistent with a very simple model of sublimation of a surface species in radiative equilibrium with the Sun. The inferred enthalpy of sublimation matches those of CO2 and NH3. More volatile species, such as N2, CH4, and CO, must be far less abundant on the sublimating surfaces.